Field reports, Tanya E. Bray, summer 1990 - Bray, Tanyaet al (1990)
Field reports submitted by Tanya E. Bray with several additional observers with a detailed descriptions of certain sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1990. Epson - sheet feed/flatbed